PROMOTING SUSTAINABLE FASHION EDUCATION THROUGH TRADITIONAL EMBROIDERY FOR STUDENTS - Nematova Tursuntosh Alisher qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores how traditional embroidery can be used to promote sustainable fashion education among students. Integrating heritage embroidery techniques into fashion and textile projects encourages creative design, resource-conscious practices, and cultural awareness. The study examines pedagogical methods for teaching sustainability through traditional crafts, highlighting the benefits of hands-on workshops. Research shows that such projects enhance students’ artistic skills, innovative thinking, and understanding of sustainable design principles.